382 Targeting innate immunity with BXCL701 in combination with pembrolizumab in patients with advanced solid cancers: phase 2 basket study. (9th November 2020) - Janku, Filip; Tsimberidou, Apostolia; Holley, Veronica; Adat, Abha; Karakuzu, Ozgur; Call, Greg; Urschel, Gabriele; Healey, Diane; O'Neill, Vincent
Abstract : Background: BXCL701 is an oral competitive inhibitor of DPPs, primarily DPP8/9, that activates inflammasome mediated pyroptosis. BXCL701 therefore, can induce an innate immune reaction and tumor inflammation, bridging between innate and adaptive immunity, potentially leading to synergistic anticancer activity when combined with PD-1 antibody pembrolizumab. Methods: This is a phase 2, open-label, single-center study (NCT04171219 ) of oral BXCL701 0.3 mg BID on days 1–14 and intravenous pembrolizumab 200 mg on day 1 of a 21-day cycle with a safety lead-in to evaluate RECIST/iRECIST response rate in patients with advanced solid cancers. After confirming safety and dose limiting toxicities (DLT) in the first 6 patients, additional patients are being enrolled to a PD-1/PD-L1 antibodies (ab) naïve cohort and PD-1/PD-L1 ab pretreated cohort. Each cohort is planned to enroll 9 patients, and if a partial (PR) or complete response (CR) is observed the cohort is expanded to a total of 17 patients. The treatment is considered promising if at least 3 PRs or CRs are observed in a cohort of 17 patients. Results: As of August 24, 2020, 14 patients were treated; 5 patients (prostate cancer, endometrial cancer, uveal melanoma, liposarcoma, basal cell carcinoma) were enrolled in the PD-1/PD-L1 ab naïve cohort and 9 patients (leiomyosarcoma, squamous cell carcinoma of unknown primary, melanoma, myxoid sarcoma, pleomorphic sarcoma, colorectal cancer, anaplastic astrocytoma, prostate cancer) were enrolled to PD-1/PD-L1 ab pretreated cohort. Among all 14 patients, there was 1 episode of grade 4 hypotension (recovered) and 1 episode of grade 5 hypotension attributed to BXCL701. In the PD-1/PD-L1 ab naïve cohort, of 3 patients with available imaging, 2 had a PR (uveal melanoma previously treated with PD-1/OX40 fusion protein [-31%] n=1; and microsatellite stable endometrial cancer [-62%], n=1). In the PD-1/PD-L1 ab pretreated cohort, there were no objective responses in 5 patients with available imaging; however, a patient with pleomorphic sarcoma refractory to PD-1 antibody monotherapy demonstrated a tumor shrinkage of -18% on the first restaging imaging. Conclusions: BXCL701 in combination with pembrolizumab demonstrated encouraging signals of activity in selected difficult-to-treat cancers. Mitigation strategies to prevent events of high-grade hypotension are being implemented to allow the enrollment continuation. Trial Registration: NCT04171219 Ethics Approval: The study was approved by MD Anderson IRB